Advanced vibro-acoustic condensed models for multi-layer structures - Uthayasuriyan, Arasan (2022)
This thesis concerns the development of analytical condensed models to predict the vibroacoustic responses of planar multi-layer structures. Typical structural components in, e.g., aerospace applications involve multi-layer composite panels and evaluation of vibroacoustic indicators (for example, transmission loss) of these multi-layer structures through finite element analysis would result in expensive computational power and time. This is due to an increase in the total number of degrees of freedom which results from a complete description of each different layer in the multi-layer system. This challenge could be tackled by employing a condensed and equivalent single layer that simulates the vibroacoustic behaviour of the multi-layer system which would require lesser computational storage that effectively reduces the computation time. In addition, condensed models enable us to understand the physical behaviour of the multi-layers at different frequency regimes. The existing equivalent plate models describe the propagation of bending and shear waves in multilayers, giving a useful prediction for vibroacoustic indicators across the range of audible frequencies if the multilayer structure does not contain soft material in terms of longitudinal compression. As the compressional (or dilatational) wave propagation is not employed in current models, they are applicable only to relatively thin multilayer systems.